Measuring credit risk - Coyle, Brian (Canterbury : CIB Publishing, 2000)
It explains the role played by credit rating agencies and the nature of information supplied. It also explains what other sources of information can be obtained. Having established the kind of information that is necessary to gauge the level of credit risk, the manual examines in turn the various methods of assessing different industries.
Includes index.
oif 26/08/15
Loans
Keywords: Credit scoring systems; Credit risk; Risk management